Extraction and structural properties of Acanthophora muscoides (Rhodophyceae) extracellular matrix sulfated polysaccharides and their effects on coagulation (Acta Scientiarum. Technology, 2016)
Acanthophora muscoides (Rhodophyta) contains structurally heterogeneous sulfated polysaccharides (Am-SPs) with pharmacological importance; however, its matrix SPs composition has not been still extensively investigated. This study sequentially extracted and compared the structural features and the in vitro anticoagulant effects of the Am-SPs. Papain-extraction sequence yielded Am.E-1, Am.E-2 and Am.E-3 containing differences among the relative proportions of sulfate (26.18-33%) and hexoses (42.02-60.67%) based on chemical analyses. One- (1H) and two-dimensions (1H/13C) nuclear magnetic resonance experiments showed very complex Am-SPs composed of alternating 4-linked-Î±-galactopyranosyl units and 3-linked-Î²-galactopyranosyl units presenting variable sulfation, CH3 substitutions and3,6-anhydro-Î±-L-galactose units and pyruvated-D-galactose residues, respectively, typical of agarocolloids. Different chromatographic profiles (DEAE-cellulose) were observed, with fractions (Am I, Am II and Am III eluted with 0.5, 0.75 and/or 1 M of NaCl, respectively) revealing charge density patterns and distinct mobility to heparin by agarose-electrophoresis and, when analyzed by polyacrylamide-electrophoresis, a dispersive migration and similar mobility as chondroitin-6-sulfate for Am I fractions were noted. Regarding the activated partial thromboplastin time test, fractions had no virtually anticoagulation (1.47â†’3.07 IU mg-1) in comparison with 193 IU mg-1 heparin. Therefore, Am-SPs show significantly lower anticoagulation than heparin.Â